Graves’ thyrotoxicosis as a manifestation Of immune reconstitution inflammatory syndrome in HIV patients on antiretroviral therapy - Goh, Kian Guan; Zakaria, Miza Hiryanti; Shahar, Mohammad Arif; Omar, Ahmad Marzuki (2017)
Background: A 47-year-old lady with HIVV infection presented with progressive weight loss, heat intolerance and tremor 46 months after initiation of antiretroviral therapy (ART). No previous thyroid disorders or significant family history. She has bilateral exophthalmos and diffuse neck swelling. Laboratory findings showed high level of thyroxine and suppressed thyroid-stimulating hormone (TSH). Anti-thyroglobulin (Anti-TG) and anti-thyroperoxidase (Anti-TPO) level were levated (4619.933 IU/mL and 359.745 IU/mL respectively). HIV viral loas was not detected since 32 months post ART. Her CD4 count maintained between 280-400. Treatment: She was started on oral carbimazole 30mg daily and subsequently tapered down. The symptoms of thyrotoxicosis were controlled after initiation of antithyroid. Her ART regime initially was stavudine/lamivudine/nevirapine; changed to zidovudine/lamivudine/efavirenz after trend of CD4 counts showing reduction. The regime was switched to zidovudine/lamivudine/nevirapine after the diagnosis of Graves’ IRIS. Discussion: Graves disease is a recognized manifestation of organ-specific immune reconstitution inflammatory syndrome. This is postulated as re-expansion of naïve CD4 cells after suppression of the HIV virus. Mean time until development of Graves’ disease is between 8-53 months post-treatment. In this case, she developed thyrotoxicosis symptoms at 46 months. In a large single centre cohort study, non-nucleoside reverse transcriptase, particularly efavirenz, is associated with hyperthyroidism and protease inhibitors is related to hypothyroidism. However, our patient received short duration (2 months) of efavirenz before changing to other ART. The recovery of CD4 counts coupled with detection of antithyroid antibodies makes it more likely to be Graves’ IRIS. Conclusion: Graves’ IRIS is a rare manifestation of thyrotoxicosis among ART-treated HIV patients. It must be suspected if patinets exhibit thyrotoxicosis symptoms. Further studies are required to determine the effect of ART in development of autoimmunity in the thyroid gland.